Pemanfaatan Teks Multimodal dalam Perancangan Soal Literasi Bagi Guru Bahasa Indonesia SMP Se-Kabupaten Sragen - Joko Purwanto; Umi Faizah; Dea Permataningtyas; Riska Amelia; Tarisa Finanda (Lembaga Pengembangan Kinerja Dosen, 2025)
The need to strengthen literacy in Indonesian language learning requires teachers to be innovative in designing assessment instruments that are relevant to current developments. One approach that can be used is the application of multimodal texts, namely texts that combine various communication modes such as writing, images, sound, and symbols to convey meaning more comprehensively. This community service program was carried out with the aim of improving the competence of Indonesian language teachers at the junior high school level throughout Sragen Regency in developing literacy questions based on multimodal texts that align with the demands of the Independent Curriculum. The activity was carried out through two months of intensive training and mentoring, which included a theoretical understanding of the concept of multimodal texts, analysis of sample questions, and practice in developing literacy-based assessment instruments. The results of the activity showed a significant increase in teachers' understanding of the principles of multimodal texts and their ability to design questions that challenge students' critical and creative thinking skills. Through this program, teachers not only gained new knowledge but also were motivated to be more adaptive to developments in digital media and innovation in learning. Thus, this activity contributed to improving the quality of Indonesian language learning that is contextual, interactive, and meaningful for students.